DEVELOPMENT OF NONVERBAL COMMUNICATION BASED ON THE USE OF VISUAL TOOLS IN CHILDREN WITH AUTISM SPECTRUM - Mamatova Aziza Bo‘riboyevna; Muhammadsharipova Nafisa Saidakbarovna (Bright Mind Publishing, 2025)
The article provides information on the specifics of verbal and non-verbal communication skills of children with autism spectrum, the deficiencies encountered in the speech of such children, as well as methods of correcting these deficiencies by speech and non-verbal methods.
Keywords: Autism syndrome, speech and communication, verbal and non-verbal communication, PECS cards, exolalia, apraxia, mutism, prosodic.